Treatment of Genital Lymphedema With Lymphatic System Pedicled SCIP Transfer in Combination With Nanofibrillar Collagen Scaffolfds - Sergi Barrantes, MD; Sílvia de la Torre, MD; Giuseppe Visconti, MD, PhD; Marc Blasi, MD; Anna López-Ojeda, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Genital lymphedema is a challenging condition often refractory to conservative treatments. This case report presents a novel surgical approach combining a lymphatic system transfer based on a pedicled superficial circumflex iliac perforator flap with nanofibrillar collagen scaffolds to address genital lymphedema secondary to hidradenitis suppurativa. A 47-year-old man with hidradenitis suppurativa–related genital lymphedema, unresponsive to conservative measures, underwent the procedure. Indocyanine green lymphography and ultrahigh-frequency ultrasound were used for preoperative flap planning, including lymphatic vessels in the skin paddle. Nanofibrillar collagen scaffolds were placed to enhance lymphangiogenesis in distal genital areas. The patient experienced significant improvement, with a reduction in lymphedema severity from 5 of 9 to 1 of 9 on the Genital Lymphedema Score and substantial relief of symptoms. Single-photon emission computed tomography demonstrated uptake of 18F-fluorodeoxyglucose at the right inguinal lymph nodes, ipsilateral to the lymphatic flap. This case demonstrates the potential of this combined approach in managing complex genital lymphedema.